Kinetic and mechanistic release studies on hyaluronan hydrogels for their potential use as a pH-responsive drug delivery device - Erikci, Saliha; Bergh, Niklas van den; Böhm, Heike (Gels, 2024)
Hyaluronic acid, a biocompatible polymer, holds significant potential for drug delivery applications. Its variable degree of protonation, which entails tunable physical properties, makes it an ideal candidate for developing pH-sensitive hydrogels. Like other smart drug delivery systems, pH-responsive hydrogels can enhance medical treatment and expedite the healing process. However, the inherent complexity of hydrogels poses challenges in identifying suitable matrix systems. This study evaluates the potential of thiolated hyaluronic acid hydrogels, physically cross-linked with deacetylated disaccharide units of the polymer, for use in drug delivery. Using low-molecular-weight dextrans as model drugs, we investigated the system’s response to different pH environments in terms of swelling as well as the kinetic and mechanistic release of the encapsulated compound. The data suggest tunable release properties of the gel regarding drug size and pH value. Our results demonstrate the gel system’s potential for smart drug delivery. We anticipate that this system is a promising candidate for use in transdermal wound healing applications and strongly encourage further investigations using other sorts of (model) drugs to gain a more detailed insight into its pH-responsive transport qualities.
Gesehen am 02.06.2025